EFEKTIVITAS PENEGAKAN HUKUM TERHADAP PELAKU KEKERASAN SEKSUAL ANAK DI KOTA SERANG: ANALISIS PUTUSAN PENGADILAN - Amelia Putri; Ines Putri Ramadhani; Evan Falah Pratama (PT. Hasba Edukasi Mandiri, 2025)
Sexual violence against children is a serious crime that has a long-term impact on victims and society. Based on concerns that normative provisions are not sufficient to ensure law enforcement that is responsive to the protection needs of child victims in Serang City, this study aims to analyze the effectiveness of law enforcement against perpetrators of sexual violence against children in Serang City, with a focus on analyzing court decisions. The research method used is normative juridical with a legislative approach and a case approach. The results show that normatively, the legal framework is adequate, but in practice there are still obstacles in terms of evidence, judicial considerations, and consistency of punishment. This study concludes that the effectiveness of law enforcement is not yet optimal and requires strengthening in terms of victim protection, quality of evidence, and consistency of verdicts.